Overcoming Deepfake Porn Crimes In Indonesia - Andira, Sindi Ayu; Susila, M. Endriyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The research aims to look at dealing with deepfake porn crimes in Indonesia. The method used in normative legal research with the data sources used is primary, secondary, and tertiary legal materials to support the research. Research results show that in Indonesia, there are no regulations that specifically and comprehensively regulate the misuse of AI in the form of deepfake porn. Based on the many types of crimes committed by deepfake porn perpetrators in the process of making deepfake porn videos, the legal provisions that can be applied to these crimes also vary. The rise of deepfake porn in Indonesia, which is spread on the internet, is causing harm to other people. Therefore, serious countermeasures are needed from various parties, including law enforcement officials who have made efforts to combat deepfake porn crimes on the internet. Countermeasures against deepfake porn crimes consist of implementing preventive efforts in the form of outreach to the public and taking firm action against perpetrators of crimes. deepfake porn invites the public to play an active role in reporting deepfake porn crimes, preventing the spread of deepfake porn videos on the internet, and implementing repressive efforts in the form of actions taken by law enforcement officials such as conducting inquiries, investigations, prosecutions and examinations in court.